(untitled) (Tribhuvan University Journal of Microbiology, 2025)
Objectives: The purpose of the study was to identify the bacterial species in fishes as well as to enumerate the total viable count and total coliform count in the fish sample from Kathmandu valley market. Methods: A descriptive study was conducted where two species of fish i.e., Rohu and Bachua, were collected from several shops within the Kathmandu valley. Each fish was separated into gills, gut, and skin portions, constituting a total of 18 samples and the samples were then processed according to standard laboratory methods for the isolation and identification of bacteriological species. Results: In a total sample size of 18 samples, 44 isolates were isolated where 20.46% of the isolates were found to be gram-positive bacteria and 79.54% of the isolates were found to be gram-negative bacteria. Escherichia coli accounted for 38.64%, resulting in being the dominant organism. The sample collected from Kalimati in Bachuwa showed the highest bacterial count (1.01×107cfu/gm) while the sample from Lalitpur in Rohu showed the lowest bacterial load (9.68×104cfu/gm). In Rohu samples, the highest coliform load and lowest coliform load was collected from Kalimati (4.25×105cfu/gm) and Lalitpur (3.78×103cfu/gm), respectively. Conclusion: The highest bacterial load, coliform load and isolated pathogens in fishes available in the market of Kathmandu valley from this study concluded that the fishes are highly vulnerable to bacterial contamination, and suggest the potential risk for public’s health issues.